Survey on Solution Providers of Hybrid Cloud Computing - Rajeswari, S. (IJRDO -Journal of Computer Science Engineering, 2016)
Cloud computing is spreading around the enterprise world, eliminates the requirement for setting high-cost computing infrastructure and services for IT solutions. With its potential, cloud computing allows numerous and varied increase in capacity and capabilities of the existing technology by the need of extending the technology across variety of clouds for inter cloud communication. “Hybrid cloud” as a latest buzz word is the deployment of contact between private, public and community clouds for the necessary of application, services and data migration. With its diverse services like SaaS, PaaS and IaaS, the hybrid cloud has made resources which was once never available on scalable and demand manner. This extensive survey paper aims to elaborate and analyze the numerous hybrid cloud computing service providers of which will provide the transparency of features, profits, fitting together clouds, choosing service providers, implementation and functionality based on internal and external resources. Each hybrid cloud solutions of this era are briefed for benefiting any organizations for deciding on a hybrid cloud provider. The objective of this paper is to review comprehensively the current hybrid cloud providers so that interested c-level executives of the enterprises in adoption of hybrid cloud could gain knowledge over the hybrid cloud solution providers and will give their organization an edge over competitors.